(untitled) (Universal International Scientific Journal, 2026)
This article provides a scientific and theoretical analysis of the psychological criteria for the effective adaptation of future specialists to professional activity. The study highlights the psychological factors of the process of professional adaptation, the motivational, cognitive and communicative characteristics of the individual, and their impact on the effectiveness of professional activity. It also analyzes the main criteria that determine the level of adaptation of future specialists to professional activity - professional motivation, socio-psychological adaptation, communicative competence, stress tolerance and reflexive abilities. According to the results of the study, these criteria are important psychological conditions for the successful entry into professional activity and professional development of a specialist